Muscle Power After Stroke - Stavric, Verna A (Auckland University of Technology, 2007)
Stroke is the leading cause of disability worldwide. It often leads to mobility limitations resulting from deficits in muscle performance. While reduced muscle strength and rate of force production have been reported, little is known about the power generating capability of people after stroke and its relationship to mobility. Research in other populations has found that measures of muscle power may have a greater association with activity performance than do measures of muscle force alone. Consequently, in an attempt to optimise power, investigators have focused on identifying ideal parameters within which to train for power. One such parameter is the identification of the loading level at which maximal power is generated. Literature reporting optimal loads from both young athletic and healthy older populations has yielded mixed results, making the applicability to a hemiparetic population difficult. The purpose of this study was to investigate muscle power performance at differing loads and to determine at what load muscle power is best elicited in hemiparetic and age and gender matched control groups. A secondary aim was to ascertain whether there is a relationship between the muscle power values obtained and activities such as gait, stair climbing and standing from a chair. Twenty nine hemiparetic volunteers and twenty nine age and gender matched controls were evaluated. Involved and uninvolved legs of the stroke group and a comparison leg of the control group underwent testing. Leg press muscle power was measured using a modified supine leg press machine at 30%, 50% and 70% of a one-repetition maximum (1-RM) load. Participants were positioned on the leg press machine and asked to push, with a single leg, as hard and as fast as they could. Data was collected via a mounted force platform and a linear transducer connected to a platform on which the participants lay. From these, power was able to be calculated. The activities were timed while being performed as fast as possible. The results showed that peak muscle power values differed significantly between the involved, uninvolved and control legs. Peak leg power in all three leg groups was greatest when pushing against a load of 30% of 1-RM. Involved leg peak power tested at 30% of 1-RM (Mean:240; SD:145 W) was significantly lower (p<0.05) than the uninvolved leg (Mean:506; SD:243 W). Both the involved and uninvolved legs generated significantly lower peak power (p<0.05) than the control leg (Mean:757; SD:292 W). Correlations were found between the involved leg peak power and gait speed and involved leg peak power and stair climbing (r=0.6-0.7, p<0.05). No correlation was found between paretic leg peak power and chair stands. The control group leg peak power demonstrated significant associations with the performance of all three activities.In summary, there were significant differences between the involved and the uninvolved leg in power production after stroke. As well, there are significant differences between the uninvolved leg and the leg of those not affected by stroke. Power was related to a number of activities.
Keywords: Stroke; Older adult; Muscle power; Activity performance; Muscle strength; Cross-sectional design